Intervention strategies for urban blight: a participatory approach - Costa, J.; Ferreira, F.; Spahr, R.; Sunderman, M.; Pereira, L. (Sustainable Cities and Society, 2021)
Urban blight has been the subject of numerous worldwide studies. However, because of blight’s complexity, direct relationship with urban planning and multifaceted associated variables, studies targeting certain aspects of blight require detailed conceptualization and structure to facilitate decision-making processes that address blight. Many urban, socio-economic and cultural externalities associated with blight need to be addressed in developing viable intervention strategies for prevention, attenuation and eradication. Identifying and simplifying the complex issues associated with blight is important as their intricacy creates difficulties for decision makers. We simplify the blight problem by using unique techniques for structuring complex decision problems (i.e., problem structuring methods (PSMs)). This methodology is based on multiple-criteria decision analysis (MCDA) principles, as well as a combination of participatory techniques (i.e., decision conferencing and cognitive mapping). In a subsequent phase, the decision-making trial and evaluation laboratory (DEMATEL) technique is used to enable the development of a more realistic, transparent analysis model for blight intervention strategies. This study assumes a constructivist logic, so both objective and subjective elements are included. The proposed methodology’s advantages and limitations are also discussed.